Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3382/ps.2013-03086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the commercial in ovo injection of 25-hydroxycholecalciferol on the hatchability and hatching chick quality of broilers

Abstract: The effects of the in ovo injection of commercial diluent containing various levels of 25-hydroxycholecalciferol [25(OH)D3] on hatchability and hatching chick quality variables in Ross × Ross 708 broilers were examined in 2 trials. All treatment groups, each containing 21 and 40 eggs in trials 1 and 2, respectively, were randomly represented on each of 10 replicate tray levels of a single-stage incubator. On 18 d of incubation (doi), eggs were subjected to 1 of 6 treatments using a commercial multi-egg injecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“…The in-ovo method was first used by Sharma & Burmester (1982) for the vaccination of turkey hatching eggs against Marek's disease. Recently, the in-ovo method has been investigated by researchers for administering ascorbic acid (Elibol et al, 2001;Ipek et al, 2004;Sgavioli et al, 2015), carbohydrates (Zhai et al, 2011;Salmanzadeh, 2012;Ipek et al, 2004;Tako et al, 2004), amino acids (Bhanja et al, 2014;Ohta et al, 1999;Kermanshahi et al, 2015), vitamins (Bello et al, 2013;Salary et al, 2014), minerals (Yair et al, 2013;Oliveira et al, 2015), pollen (Coskun et al, 2014), hormones (Moore et al, 1994;Kocamis et al, 1999), and royal jelly (Moghaddam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The in-ovo method was first used by Sharma & Burmester (1982) for the vaccination of turkey hatching eggs against Marek's disease. Recently, the in-ovo method has been investigated by researchers for administering ascorbic acid (Elibol et al, 2001;Ipek et al, 2004;Sgavioli et al, 2015), carbohydrates (Zhai et al, 2011;Salmanzadeh, 2012;Ipek et al, 2004;Tako et al, 2004), amino acids (Bhanja et al, 2014;Ohta et al, 1999;Kermanshahi et al, 2015), vitamins (Bello et al, 2013;Salary et al, 2014), minerals (Yair et al, 2013;Oliveira et al, 2015), pollen (Coskun et al, 2014), hormones (Moore et al, 1994;Kocamis et al, 1999), and royal jelly (Moghaddam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the noted increase in bone strength on d 28 poh that was reflected by an increased BBS in the diluent-injected males of this study may be related to an increase in their bone Ca concentrations (McDevitt et al, 2006). Bello et al (2013) showed that the in ovo injection of 25(oH)D 3 increased its subsequent concentration in the systemic circulation of broilers. Furthermore, in another previous study, Soares et al (1995) affirmed that an increase in the intake of 25(oH)D 3 or other forms of vitamin D 3 resulted in higher systemic concentrations of Ca.…”
Section: Discussionmentioning
confidence: 84%
“…Injections were performed using an Intelliject multi-egg injector (Avitech LLC, Salisbury, MD). Validation of the site of injection (amnion), injection needle dimensions and egg penetration depth, egg handling, and in ovo injection automation were as described in detail by Bello et al (2013). In addition, preparation of the injected solutions using crystalline 25(oH) D 3 (DSM Nutritional Products Inc., Parsippany, NJ) was as described by Bello et al (2013Bello et al ( , 2014a.…”
Section: Egg Injection and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations